The influence of stress, coping mechanisms and psychological symptoms on inflammatory bowel disease activity: A retrospective case-control analysis - Shirvani, Javad Shokri; Petrodi, Seyed Taher Hashemi; Shirafkan, Hoda; Shahrokhi, Shirin; Faramarzi, Mahbobeh (Indian journal of gastroenterology, 2025)
Background and Objectives Psychological stress is widely recognized as a key factor that can initiate or aggravate symptoms in patients with inflammatory bowel disease (IBD). This research was aimed at examining the influence of stressors, coping mechanisms and psychological symptoms on disease activity in patients with Crohn’s disease (CD) and ulcerative colitis (UC). Methods A retrospective case-control research was performed with 138 patients diagnosed with IBD (76 with CD and 62 with UC). The participants were categorized into case groups (active disease: 31 CD, 38 UC) and control groups (inactive disease: 31 CD, 38 UC), with matching on demographic and clinical characteristics. Each participant completed several assessments such as the Simple Clinical Colitis Activity Index (SCCAI), the Harvey-Bradshaw index (HBI), the Life Distress Inventory (LDI), the Symptom Checklist (SCL-25) and the Coping Inventory for Stressful Situations (CISS-21). Results Participants experiencing active disease reported higher levels of life stress, with mean scores of 65.42 ± 8.88 in CD and 65.42 ± 8.88 in UC, in comparison with 45.97 ± 13.23 and 41.79 ± 13.49, respectively, in those with inactive disease. Additionally, psychological symptoms were more prevalent in both CD group (57.00 ± 12.71 vs. 47.39 ± 14.65) and the UC group (57.80 ± 9.82 vs. 40.05 ± 11.23) with active disease. Patients with active disease were more likely to employ coping strategies centered on avoidance, emotional responses and tasks than those without disease activity. Logistic regression analysis identified life stress ( p < 0.001, 95% CI = [1.06–1.18], B = 1.24) and emotion-focused coping strategies ( p < 0.001, 95% CI = [1.26–1.88], B = 1.54) as notable predictors of disease activity, whereas task-focused coping emerged as a protective factor ( p < 0.029, 95% CI = [1.68–1.98], B = 1.81). Conclusion This research underscores the critical role of managing stress and adopting effective coping mechanisms in reducing the likelihood of disease flare-ups in IBD subjects. Healthcare providers should prioritize integrating these approaches into treatment protocols for IBD management. Graphical Abstract